Evaluasi Kualitas Visual Objek Wisata Pesisir Pantai Kota Makassar Berbasis Scenic Beauty Estimation (SBE) - Nurwajehi Nurwajehi; Slamet Trisutomo; Sri Aliah Ekawati (Jurnal Wilayah & Kota Maritim (Journal of Regional and Maritime City Studies), 2019)
Coastal areas have high potential of natural and visual resources both natural and built.This condition makes the coastal area in Makassar City one of the local and foreign destinations. Beautiful visuals are one of the factors driving a region to visit to release fatigue from work routines.However, the arrangement of coastal tourism in Makassar City is currently not suitable so that the visual potential cannot be utilized optimally.This study aims to evaluate the visual quality of the coast of Makassar City (Losari Beach, Akkarena Beach and Tanjung Bayang Beach) using the Scenic Beauty Estimation (SBE) method.The results of the assessment of the visual quality of coastal attractions based on Scenic Beauty Estimation (SBE) are grouped into quality and cleanliness, beauty (low, medium, high) quality.